2021
DOI: 10.1111/imm.13318
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic‐translocated Ku70 senses intracellular DNA and mediates interferon‐lambda1 induction

Abstract: We have previously identified that human Ku70, a nuclear protein, serves as a cytosolic DNA sensor. Upon transfection with DNA or infection with DNA virus, Ku70 translocates from the nucleus into the cytoplasm and then predominately induces interferon lambda1 (IFN-k1) rather than IFN-alpha or IFN-beta, through a STING-dependent signalling pathway. However, a detailed mechanism for Ku70 cytoplasmic translocation and its correlation with IFN-k1 induction have not been fully elucidated. Here, we observed that cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 70 publications
5
31
0
Order By: Relevance
“…All this happened before IFN-l1 induction. Consequently, it is reasonable to speculate that the translocation of Ku70 happened first and that IFN-l1 induction occurred later since we further confirmed that recombinant IFN-l1 does not induce the cytoplasmic translocation of Ku70 (Sui et al, 2021). Like Ku70, IFI16, another DNA sensor protein, has been reported to recognize and sense DNA not only in the cytoplasm but also in the nucleus of the cells, and its sensing capabilities depend on the distribution of IFI16 (Li et al, 2012;Dell'oste et al, 2014;Ansari et al, 2015).…”
Section: The Cytoplasmic Translocation Of Ku70 Is the Initial Step For Ku70 As A Cytosolic Dna Sensorsupporting
confidence: 69%
See 4 more Smart Citations
“…All this happened before IFN-l1 induction. Consequently, it is reasonable to speculate that the translocation of Ku70 happened first and that IFN-l1 induction occurred later since we further confirmed that recombinant IFN-l1 does not induce the cytoplasmic translocation of Ku70 (Sui et al, 2021). Like Ku70, IFI16, another DNA sensor protein, has been reported to recognize and sense DNA not only in the cytoplasm but also in the nucleus of the cells, and its sensing capabilities depend on the distribution of IFI16 (Li et al, 2012;Dell'oste et al, 2014;Ansari et al, 2015).…”
Section: The Cytoplasmic Translocation Of Ku70 Is the Initial Step For Ku70 As A Cytosolic Dna Sensorsupporting
confidence: 69%
“…Ku70 cytoplasmic translocation and IFN-l1 induction only in HEK cells infected with the HSV-1 McKrae strain. Those results further emphasized that the cytoplasmic translocation of Ku70 is a required step for Ku70-mediated IFN-l1 induction (Sui et al, 2021). A quantification analysis with Western blot using cytosolic fractions was adapted to characterize the accumulation kinetics of cytoplasmic Ku70.…”
Section: The Cytoplasmic Translocation Of Ku70 Is the Initial Step For Ku70 As A Cytosolic Dna Sensormentioning
confidence: 94%
See 3 more Smart Citations